Board Games Come Back. - Choi Byung-il (Koreana)
The article focuses on the revival of board games cafés, particularly near universities, in South Korea. Topics discussed include the challenges faced by board game cafés in terms of slow customer turnover, the role of technology and internet on the revival of board games, and the 2018 Seuollo Board Game Championships held in Malli-dong Plaza in Seoul. It also mentions the benefits of board games including on character development, family bonding, and socialization with strangers.